Project-Based Learning as a Method to Strengthen Communication: Students' Insights in Business English Education - Erna Dwinata; Rosanita Tritias Utami (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study examines students' perceptions of Project-Based Learning (PBL) in the "English for Business communication" course at Universitas Bhinneka. PBL, a student-centered approach, engages students in meaningful projects, promoting skills like collaboration, communication, problem-solving, and critical thinking. The course was divided into three phases: Product Identification and Presentation, Business Communication via Email, and Field Observation and Product Promotion. The study involved 30 second-semester Economics Education students, utilizing questionnaires to gather data. Findings indicate that students found PBL to be an effective and engaging teaching method. The activities helped them develop public speaking, formal writing, and professional communication skills. The hands-on nature of PBL allowed students to apply theoretical knowledge in real-world contexts, particularly in business scenarios. They appreciated the practical applications of their tasks and the opportunity to work collaboratively with peers, which enhanced their learning experience. While some challenges, such as the need for careful planning and adequate resources, were noted, students generally reported increased motivation and engagement. The study concludes that PBL is a valuable method for teaching English in a business context, providing practical and relevant learning experiences.